The Role of Cryptographic Tokens and ICOs in Fostering Platform Adoption - Yannis Bakos; Hanna Halaburda (Center for Economic Studies and ifo Institute (CESifo), 2019)
Platform-specific digital tokens are becoming increasingly common with the proliferation of initial coin offerings (ICOs). In addition to a novel financing mechanism, such tokens can help address the coordination problem that is common in network adoption. We develop a model to investigate the use of tradable digital tokens to solve this coordination problem. Our analysis shows that platform-specific tokens, due to their tradability and consequent higher value if the platform succeeds, can provide another tool to overcome the coordination problem in a platform adoption setting and to support equilibria favorable to the platform. We find that if the platform is not facing capital constraints, the most profitable strategy is the traditional strategy to subsidize adoption. If the platform is capital constrained, however, then token issuance provides an alternative that is increasingly attractive as the platform's cost of capital increases. With tokens, the platform trades off future revenue for present revenue, which helps finance solving the coordination problem. In that sense, even pure utility tokens have certain characteristics of equity: (1) early adopters share the future gains if the platform succeeds, and (2) the tokens provide an alternative when traditional financing is too costly or not available to the platform.
Keywords: D80; G20; O30; 330; economics of IS; ICOs; blockchain; platforms; network effects